2017
DOI: 10.3389/fpsyt.2017.00208
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Experience at Different Trimesters during Pregnancy Is Associated with Leukocyte Telomere Length and Long-term Health in Adulthood

Abstract: Leukocyte telomere length (LTL) is a predictor of age-related diseases, cancer, and even early mortality. Prenatal stress experience has been suggested to associate with short LTL and an increased disease risk in adult life. The present study aimed to evaluate the 39-year effects of prenatal earthquake stress (PES) exposure on LTL and increased age-related disease risk in adulthood. Here, we compared the LTL in the subjects who were exposed to PES to healthy controls (CN) and evaluated whether stress exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
1
13
0
3
Order By: Relevance
“…This tendency was associated with a higher rate of macrosomia among this population. Notably, along the same line, Wang et al . found that women exposed to prenatal earthquake stress in the mid‐to‐late period of pregnancy had significantly shorter leukocyte telomere length, a factor related to age‐related diseases such as cancer and early mortality, as compared with women exposed in the early period of pregnancy.…”
Section: Discussionmentioning
confidence: 83%
“…This tendency was associated with a higher rate of macrosomia among this population. Notably, along the same line, Wang et al . found that women exposed to prenatal earthquake stress in the mid‐to‐late period of pregnancy had significantly shorter leukocyte telomere length, a factor related to age‐related diseases such as cancer and early mortality, as compared with women exposed in the early period of pregnancy.…”
Section: Discussionmentioning
confidence: 83%
“…Table SI 11.3 shows data collected on the relationship between PS and offspring's glucose metabolism. Four studies on offspring's glucose and PS were identified in our review and all of them found no association between glucose and PS (negative life events, job strain and exposure to earthquake) [41,47,54,55]. We found only one study reporting on PS and insulin without significant assoaciations [41].…”
Section: Systematic Review On the Relationship Between Ps And Blood Pmentioning
confidence: 82%
“…Two separate studies described the relationship between maternal exposure to earthquake during pregnancy (as a surrogate for PS) and blood pressure later in adult life. In one study, the systolic pressure was significantly higher in the prenatal earthquake stress group compared to that in the control group, but no significant differences were found for diastolic pressure [55]. In the other study, prenatal exposure to the earthquake was not associated with systolic or diastolic blood pressure [47].…”
Section: Systematic Review On the Relationship Between Ps And Blood Pmentioning
confidence: 87%
See 2 more Smart Citations